Analysis of Enterprise Profile and Composition of Solid Waste Generated in the Informal Sector of Gweru, Zimbabwe. (11th June 2014) - Jerie, Steven
Abstract : This paper examines the characteristics of solid waste generated in the informal sector enterprises of Gweru, the third largest city in Zimbabwe. Samples from the informal sector enterprises were collected in plastic bags and labelled with unique identity marks. The segregated components were measured to determine percentages of total weight of a sample. The data collected during the two seasons were analysed statistically using ANOVA to identify key similarities and differences. The major components of the waste stream include food and vegetable wastes in the market areas (from 18 to 51% of total weight), metals in the industrial areas (from 19 to 36%), and paper in the residential suburbs and markets (9–11% of total weight). The biodegradable waste stream dominates in the market areas of Kudzanai and Kombayi where it constitutes an average of 57.1% of waste generated in these areas. Establishing biodegradability of solid waste is essential because the majority of environmental and health problems associated with waste generated in the enterprises are caused by the biodegradable components. In order to come up with a sustainable and comprehensive waste management plan for the informal sector of Gweru, an up-to-date database on the composition and characteristics of the waste is a primary requirement.